TEALS - Elias, Jaan, (SAGE Business cases., 2020)
In 2019, TEALS (Technology Education And Literacy in Schools), a program built to pair software engineers with high schools to develop computer literacy, faced a crossroads. Should it stay under the Microsoft philanthropic umbrella or venture out on their own?